FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN - Kartina Natalylova; Tasya Ferjiana (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of the study was to determine the impact of asset utilization, debt monitoring, profitability, liquidity, firm growth, firm size, and dividend policy on firm value. Firm value is an economic concept that reflects firm value. The population of research are non-financial companies listed on the Indonesian Stock Exchange in 2019-2021. The sampling method was used for the results of 92 non-financial corporations. This researcher tested the independent variables against the dependent variables tested using multiple linear regression. The results of this study show that profitability and firm growth affect its firm value. This means that profitability and firm growth variables are the key indicators that affect firm value. Profitability has a positive impact on firm value. Earnings growth reflects the company's development and gives investors a positive signal to raise the stock price. Firm growth has a negative impact on company value. So that companies that do not grow have poor prospects and small profits. Poor outlook affects company depreciation. Asset utilization, debt monitoring, liquidity, firm size, and dividend policy variables do not affect firm value.